2011
DOI: 10.1038/ajg.2010.340
|View full text |Cite
|
Sign up to set email alerts
|

HLA-G 14 bp Deletion/Insertion Polymorphism in Celiac Disease

Abstract: Our results also indicate that the effect of the HLA-G D/I polymorphism is restricted for HLA-DQ2, and not simply due to the presence of linkage disequilibrium with the major known risk factor; moreover we found that the presence of the I allele confers an increased risk of CD in addition to the risk conferred by HLA-DQ2 alone and that subjects that carry both DQ2 and HLA-G I alleles have an increased risk of CD than subjects that carry DQ2 but not the I allele.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 40 publications
1
18
0
1
Order By: Relevance
“…Down syndrome or autoimmune thyroid disease, were observed while there was found low or negative values in CD patients on a gluten-free diet for more than five years. Fabris et al 29 confirmed the results of Torres et al Trynka et al recently found 13 new CD risk loci, bringing the number of known loci (including HLA) to 40. 36 …”
Section: Hla-dqsupporting
confidence: 78%
See 2 more Smart Citations
“…Down syndrome or autoimmune thyroid disease, were observed while there was found low or negative values in CD patients on a gluten-free diet for more than five years. Fabris et al 29 confirmed the results of Torres et al Trynka et al recently found 13 new CD risk loci, bringing the number of known loci (including HLA) to 40. 36 …”
Section: Hla-dqsupporting
confidence: 78%
“…However, the possibility that these rare cases represent misdiagnosis must be considered. The connection between CD and HLA G 28,29 and its role in tissue typing in the clinic must be further investigated. It seems fair to conclude that if CD-like disease develops in HLA DQ2/DQ8-negative individuals, then it is very rare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are indications that through its impact on sHLA-G secretion, the HLA-G14bp ins/del polymorphism may be clinically important. The G14bp ins/ins genotype has been reported to be associated with increased risk of coronary artery disease [11], invasive cancer of the uterine cervix [12], increased risk of celiac disease [13] and increased risk of acute kidney allograft rejection [14] whereas homozygosity for G14bp del has been associated with susceptibility to active cytomegalovirus infection [15] and a low risk of rejection of heart transplants [16].…”
Section: Introductionmentioning
confidence: 99%
“…The HLA‐G gene is located on 6p21.31 and shows a deletion/insertion (del/ins) polymorphism (rs16375) of a 14‐base‐pair sequence (14 bp) in the exon 8 at the 3′ untranslated region . The presence of the 14 bp insertion allele (+14 bp) has been associated to an unstable mRNA and to a lower soluble HLA‐G (sHLA‐G) protein production, suggesting a different ability to counteract inflammation between genotypes . In obese adult subjects, it has been found an association between impaired glucose metabolism and presence of sHLA‐G, but, so far, no studies have investigated the relationship between HLA‐G 14 bp del/ins polymorphism and metabolic features of obese children and adolescents.…”
Section: Introductionmentioning
confidence: 99%